Molecular Docking Studies to Evaluate Small Molecule Inhibitors of Wnt/Betacatenin Signaling Pathway: Life Sciences-Bioinformatics For Better Health Care - Dantu Sai Shyama Lakshmi Sankari; Sai Sailaja Maka; Swetha Dalal; Chandrasekhar Chanda; Ranganadha Reddy Aluru (International Journal of Life Science and Pharma Research, 2022)
Canonical Wnt pathway or β catenin dependent pathway is one of the highly conserved signalling pathway which can control gene expression and regulate cell proliferation, cell adhesion, cell migration, cell polarity and organogenesis. Abnormal regulation of β catenin in the canonical wnt signalling pathway leads to transcription of several genes involved in oncogenic programs. Aberrant signalling of the canonical wnt pathway was observed in several types of cancers including hepatocarcinoma, colorectal cancer and lung cancer. Many small molecules were observed to have the potential to block the aberrant wnt signalling pathway by allosteric binding and inhibiting β catenin molecule. The current study involves screening for ligands which can have strong allosteric binds to β catenin and inhibit wnt signalling pathway. Molecular docking studies were used to evaluate the binding capacity of the selected ligands. Curcumin, Cardamonin, FH535 and ICRT-3 were used as ligands for the molecular docking study with β catenin binding Transcription factor -4 receptor. All chosen ligands have exhibited significant binding energies with the receptor. The highest -9.518272 kcal/mol with Cardamonin followed by -9.28359 kcal/mol with FH535, -8.422604 kcal/mol with curcumin and the least -8.407231 kcal/mol with ICRT-3. All the ligands showed at least 1 hydrogen bond with the target receptor whereas Cardamonin showed 3 hydrogen bonds. Curcumin is a close second forming 2 hydrogen bonds while FH535 and ICRT-3 form only 1 hydrogen bond. The 2D interactions of the ligand and the molecule are visualised by using chimera. We observed Cardamonin to have a very strong binding affinity with the target receptor. Cardamonin can be a suitable drug candidate and might have the potential to inhibit the β catenin dependent wnt signalling pathway.